2022
DOI: 10.1186/s12882-022-02787-7
|View full text |Cite
|
Sign up to set email alerts
|

A suspected case of hyponatraemia induced rhabdomyolysis: a case report

Abstract: Background Hyponatraemia is a documented but under-recognised cause of rhabdomyolysis, with the contrasting treatment strategies for the two conditions posing a unique challenge. Balancing the need for aggressive fluid replacement for the treatment of rhabdomyolysis, with the risk of rapidly correcting hyponatraemia is imperative. Case presentation A 52-year-old gentleman with a background of HIV infection and hypertension presented with seizures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Therefore, some studies have reported that when hypokalemia occurs, the primary disease should be treated promptly, the hypokalemia should be corrected, and relevant indicators, for example, muscle enzymes, should be monitored [45][46][47]. Severe hyponatremia can also lead to RM; although the exact pathogenesis is not clear, screening for RM should not be neglected when severe hyponatremia is present [48].…”
Section: Rm Caused By Hypothyroidismmentioning
confidence: 99%
“…Therefore, some studies have reported that when hypokalemia occurs, the primary disease should be treated promptly, the hypokalemia should be corrected, and relevant indicators, for example, muscle enzymes, should be monitored [45][46][47]. Severe hyponatremia can also lead to RM; although the exact pathogenesis is not clear, screening for RM should not be neglected when severe hyponatremia is present [48].…”
Section: Rm Caused By Hypothyroidismmentioning
confidence: 99%